Identification of Factors Responsible For Difference in Financial Performance: Identifying the factors contributing to variations in financial performance of private and public sector banks (Journal of Advances and Scholarly Researches in Allied Education, 2019)
– It is most critical to choose suitable parameter at the time of measuring financial performance of banks. Till today numerous specialists have given their opinion on parameters of financial performance of banks, even huge numbers of research are accessible on financial performance of banks which has utilized diverse parameters for measuring financial performance. Based on aftereffect of financial performance investigation, inquire about is to convey forward for identifying the variables in charge of deviation in financial performance of private and public sector banks. For identifying the elements in charge of betterpoor financial performance of privatepublic sector banks, parameters are disintegrated by using their definition.